Mitigating upstream disruptions: Effects of extended inventories in first‐ and second‐tier suppliers - Durach, Christian F.; Peers, Yuri; Wang, Yimin; Repasky, Tomas (Journal of Operations Management, 2024)
AbstractThis study examines how inventory slack at first‐ and second‐tier suppliers influences buyer performance following an upstream disruption event. We analyze secondary data from buyer, first‐tier, and second‐tier triads impacted at their upper end by the 2011 Great East Japan Earthquake. By matching buyers in affected triads with similar, largely unaffected firms, we assess post‐event performance in relation to triad inventory slack. Results show: (a) inventory slack at the first and second tiers supports buyer performance after the disruption; (b) first‐tier inventory slack has a greater impact; (c) buyers with less inventory slack can extract more value from their chains' inventories compared to those with more slack; and (d) first‐tier suppliers occupy a pivotal role in bridging the second‐tier inventories to the buyer. When competition for the first‐tier intensifies, the benefits of having first‐ and second‐tier inventory slack diminish for the buyer. A central contribution of this study is to highlight the importance of resources controlled by chain members with indirect links to the buyer and the bridging role of first‐tier suppliers. These insights suggest that for effective risk management, both direct and indirect supply chain resources and their interactions need consideration. Practically, these findings should guide supplier selection, risk management, and investments in supply chain visibility.